FREQUENCY OF HEPATITIS C IN ASYMPTOMATIC PATIENTS IN DISTRICT HEADQUARTERS HOSPITAL KOTLI, AZAD KASHMIR - Saleem, Mohammad; Ahmad, Waseem; Sarwar, Javed; Jamshed, Fareeda; Gul, Nasreen; Idrees, Muhammad (Journal of Ayub Medical College Abbottabad, 2011)
Background: Hepatitis C is a common problem in developing world. It can affect a large number of asymptomatic people in whom it may cause serious complications in long run. Moreover, these asymptomatic infected people pose a serious risk for the transmission of infection to healthy population. Objective of this study was to estimate the frequency of Hepatitis C in asymptomatic adult patients attending medical OPD of District Headquarters Hospital Kotli, Azad Kashmir, and to assess the risk factors associated with its transmission. Methods: This was a cross-sectional study that included asymptomatic patients of both genders, aged 15-80 years, attending medical OPD of District Headquarter Hospital Kotli, Azad Kashmir from January to December, 2008. They attended the OPD for problems other than Hepatitis and most of them presented with vague complaints like generalised body aches, tiredness and dyspeptic symptoms. They were randomly tested for Hepatitis C virus (HCV) antibodies by Immunochromatographic kit method. Positive samples for Hepatitis C antibodies were confirmed by third generation ELISA. Those who were confirmed were assessed for the risk factors associated with HCV transmission. Results: The study included 9,564 patients. Out of them 4,230 (44.22%) were males and 5,334 (55.77%) were females. A total of 611 (6.38%) cases were positive for HCV; 257 (6.08%) were males, and 354 (6.64%) were females. Highest frequency (36%) was found between 21 and 30 years of age, and 60.54% positive patients were 21-40 years old. Blood transfusion was the most common (34.36%) risk factor followed by history of dental procedures (24.54%). In 27.16% no risk factor could be detected. Conclusion: Frequency of Hepatitis C is quite high in our population. Rate is higher in young adults. It is needed to adopt organised preventive strategies to overcome this problem. Blood transfusion is still the most significant risk factor followed by dental and surgical procedures. Health related procedures are still not safe in our set up and need to be addressed. Keywords: Hepatitis C, Asymptomatic